(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2016)
Rhubarb (Rheum rhabarbarum) is a flowering plant species belonging to the Polygonaceae family, widely accepted in the tropics, where it is consumed fresh and processed. The objective of this study was to prepare a jam from the petiole of rhubarb (R. rhabarbarum). Five jam formulations were developed from the petiole, using white sugar and panela as sweeteners. The physicochemical and microbiological characteristics of the obtained products were evaluated. demonstrating an increase in the calcium, iron, total fiber, and moisture content in the formulations containing panela.